2003
DOI: 10.1200/jco.2003.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Involved-Field Radiotherapy Is Equally Effective and Less Toxic Compared With Extended-Field Radiotherapy After Four Cycles of Chemotherapy in Patients With Early-Stage Unfavorable Hodgkin’s Lymphoma: Results of the HD8 Trial of the German Hodgkin’s Lymphoma Study Group

Abstract: Radiotherapy volume size reduction from EF to IF after COPP + ABVD chemotherapy for two cycles produces similar results and less toxicity in patients with early-stage unfavorable HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
180
0
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 415 publications
(197 citation statements)
references
References 24 publications
5
180
0
12
Order By: Relevance
“…These findings were later confirmed by other authors (10,18,19) and the combined modality of chemotherapy plus involved-field radiotherapy has become the goldstandard treatment for low-risk HL, even for those with unfavorable risk factors. Some groups (20,21) began to defend the use of chemotherapy alone to treat HD, especially for patients with localized disease, arguing that: 1) treatment with this pure modality can be used in developing countries where there is no equipment or trained personnel for appropriate irradiation; 2) precise surgical or clinical staging would not be essential; 3) late complications in growth and second malignancy associated with radiotherapy would be avoided.…”
Section: Discussionsupporting
confidence: 58%
“…These findings were later confirmed by other authors (10,18,19) and the combined modality of chemotherapy plus involved-field radiotherapy has become the goldstandard treatment for low-risk HL, even for those with unfavorable risk factors. Some groups (20,21) began to defend the use of chemotherapy alone to treat HD, especially for patients with localized disease, arguing that: 1) treatment with this pure modality can be used in developing countries where there is no equipment or trained personnel for appropriate irradiation; 2) precise surgical or clinical staging would not be essential; 3) late complications in growth and second malignancy associated with radiotherapy would be avoided.…”
Section: Discussionsupporting
confidence: 58%
“…This is in line with the finding that extended field radiotherapy had little or no advantage over involved field radiotherapy in Hodgkin's patients when used alone or after effective chemotherapy. 3,8 In addition, subgroup analyses gave no hint that the hazard ratios may differ depending on the proportion of patients with early favorable or early unfavorable disease or the inclusion or exclusion of patients with bulky disease. However, due to the small number of trials included, reliable information from subgroup analyses is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The cure rate of patients with early stage disease is high when treated with two to six cycles of ABVD (doxorubicin, bleomycin, vinblastine, dacarbazine) chemotherapy followed by involved field radiotherapy. [3][4][5] While consolidation radiotherapy is part of treatment for patients with early stage Hodgkin's lymphoma in the ESMO clinical recommendations, 6 the NCCN guidelines 7 consider chemotherapy alone an alternative treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…44 Reductions in radiotherapy field sizes and treatment doses for HL and NHL have been made to address the known increased risks for second cancers and cardiac complications caused by radiotherapy. [45][46][47] It is only very recently, however, that epidemiology studies have shown associations between mesothelioma and radiation treatment for NHL and testicular cancer. 7,19 Travis et al 7 used SEER data through 2001, enhanced by data from other population-based registries in Canada and Europe, to identify 40,576 survivors of testicular cancer who were followed for second cancers.…”
Section: Discussionmentioning
confidence: 99%